Rancang Bangun Sistem Informasi Industri Asphalt Mixing Plant pada PT. Selo Progo Sakti - Pandowo, Hedi; Sari, Chanif Kurnia (Universitas Batanghari Jambi, 2024)
PT. Selo Progo Sakti is a company engaged in the Asphalt Mixing Plant industry. Asphalt Mixing Plant is a production equipment that produces Hotmix in the form of a mixture of asphalt with some aggregate materials used as road pavement materials. This Asphalt Mixing Plant operates for production according to orders from consumers and the character of the production results in the form of hotmix must meet certain temperature criteria for gnats to be spread out on the road media so that it must be avoided so that the product conditions do not occur at low or cold temperatures because it will harden and cannot used for road pavement. Therefore, the accuracy in delivering the product to the location where it will be held will greatly determine the quality of the production after it is held on the road. In addition, product quality is also determined from the job mix or the proportion of the material mixture that has been agreed upon in accordance with the job specifications, so it needs supervision from various parties involved in the implementation of the work. The existence of an information system is a tool for controlling production costs, in this case hotmix products produced from Asphalt Mixing Plant machines are needed to monitor every production process from several departments that have been worked on so that data management can be done quickly and accurately. Therefore, this system was built in order to overcome problems such as calculating the cost of production of hotmix for each product according to jobmix, cost control, inventory control and preparation of financial reports which can be done in one integrated information system. Tools used in making this system is Visual Basic. The application design method uses the ProtoTyping method.